Monitoring International Labor Standards: Summary of Domestic Forums - National Research Council (The National Academies Press, 2003)
Over the past half century, the international flow of goods, services, and capital has grown rapidly. Globalization creates new economic, cultural, and social opportunities, but also poses the challenge of ensuring that workers throughout the world share in these opportunities. Responding to this challenge, the U.S. government carries out a variety of policies and programs aimed at encouraging greater recognition of worker rights around the globe. The U.S. Department of State monitors worker rights abroad and reports on the status of those rights as part of its annual report to Congress in the Country Reports on Human Rights Practices. Building on this history of monitoring and encouraging worker rights around the world, the Trade Act of 2002 includes on the list of overall trade negotiating objectives of the United States, promote respect for worker rights. Monitoring International Labor Standards provides expert, science-based advice on monitoring compliance with international labor standards. This report identifies relevant, valid, reliable, and useful sources of country-level data on labor standards; assesses the quality of existing and potential data and indicators that can be used to systematically monitor labor practices and the effectiveness of enforcement in order to determine compliance with national labor legislation and international standards; identifies innovative measures to determine compliance with international labor standards on a country-by-country basis and to measure progress on improved labor legislation and enforcement; explores the relationship between labor standards compliance and national policies relating to human capital issues; and recommends sustainable reporting procedures to monitor countries' progress toward implementation of international labor standards.

Materials and Process Specifications and Standards (The National Academies Press, 1977)

Strategic Long-Term Participation by DoD in Its Manufacturing USA Institutes: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The U.S. Department of Defense (DoD) Manufacturing USA Institutes aim to protect national security and increase U.S. competitiveness in manufacturing. The domestic industrial base is critical to supporting and sustaining both military advantage and economic competitiveness. Through these institutes, the DoD is committed to domestically designing and manufacturing the most innovative defense systems. Intended as intensely collaborative applied research and development endeavors among government, industry, and academia, the institutes are envisioned to become lasting, self-sustaining national assets. A long-term strategy is needed to achieve this goal. The National Academies of Sciences, Engineering, and Medicine recently convened a workshop to discuss the long-term sustainability of the Manufacturing USA Institutes. Participants explored different perspectives across multiple disciplines, discussed public-private partnership models, and considered international programs in advanced manufacturing to inform their recommendations regarding the future of the institutes. This publication summarizes the presentations and discussions from the workshop.

Flexible Electronics for Security, Manufacturing, and Growth in the United States: Summary of a Symposium - National Research Council (The National Academies Press, 2013)
Flexible Electronics for Security, Manufacturing, and Growth in the United States is the summary of a workshop convened in September 2010 by Policy and Global Affairs' Board on Science, Technology, and Economic Policy to review challenges, plans, and opportunities for growing a robust flexible electronics industry in the United States. Business leaders, academic experts, and senior government officials met to review the role of research consortia around the world to advance flexible electronics technology. Presenters and participants sought to understand their structure, focus, funding, and likely impact, and to determine what appropriate steps the United States might consider to develop a robust flexible electronics industry. Flexible electronics refers to technologies that enable flexibility in the manufacturing process as well as flexibility as a characteristic of the final product. Features such as unconventional forms and ease of manufacturability provide important advantages for flexible electronics over conventional electronics built on rigid substrates. Today, examples of flexible electronics technologies are found in flexible flat-panel displays, medical image sensors, photovoltaic sheets, and electronic paper. Some industry experts predict that the market for global flexible electronics will experience a double digit growth rate, reaching 250 billion by 2025, but most experts believe that the United States is not currently poised to capitalize on this opportunity. Flexible Electronics for Security, Manufacturing, and Growth in the United States examines and compares selected innovation programs, both foreign and domestic, and their potential to advance the production of flexible electronics technology.

Borderline Case: International Tax Policy, Corporate Research and Development, and Investment - National Research Council
The growing integration of world markets for capital and goods, coupled with the rise of instantaneous worldwide communication, has made identification of corporations as \

Risk & Innovation: Small Companies in Six Industries: Background Papers Prepared for the NAE Risk and Innovation Study (The National Academies Press, 1996)

Corporate Approaches to Protecting Intellectual Property: Implications for U. S.-Japan High-Technology Competition: Report of a Workshop (The National Academies Press, 1994)

Industrial Ecology: U.S.-Japan Perspectives (The National Academies Press, 1994)

Immigration Policy and the Search for Skilled Workers: Summary of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2015)
The market for high-skilled workers is becoming increasingly global, as are the markets for knowledge and ideas. While high-skilled immigrants in the United States represent a much smaller proportion of the workforce than they do in countries such as Australia, Canada, and the United Kingdom, these immigrants have an important role in spurring innovation and economic growth in all countries and filling shortages in the domestic labor supply. This report summarizes the proceedings of a Fall 2014 workshop that focused on how immigration policy can be used to attract and retain foreign talent. Participants compared policies on encouraging migration and retention of skilled workers, attracting qualified foreign students and retaining them post-graduation, and input by states or provinces in immigration policies to add flexibility in countries with regional employment differences, among other topics. They also discussed how immigration policies have changed over time in response to undesired labor market outcomes and whether there was sufficient data to measure those outcomes.

Revisiting the Manufacturing USA Institutes: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The Manufacturing USA initiative seeks to reinforce U.S.-based advanced manufacturing through partnerships among industry, academia, and government. Started in 2012 and established with bipartisan support by the Revitalize American Manufacturing and Innovation Act of 2014, the initiative envisages a nationwide network of research centers for manufacturing innovation. Some 14 manufacturing innovation institutes have been established to facilitate the movement of early-stage research into proven capabilities ready for adoption by U.S. manufacturers. To better understand the role and experiences of the Manufacturing USA institutes, a committee of the National Academies of Sciences, Engineering, and Medicine convened a workshop on May 23, 2017 drawing together institute directors and manufacturing policy experts along with leaders from industry, academia, and government. Given the continued prominence of enhancing domestic manufacturing and international competitiveness in public policy discussions, the National Academies convened a second workshop on November 14, 2018, to monitor the progress of the Manufacturing USA institutes. This publication summarizes the presentations and discussions from this second workshop.

Analyzing the U.S. Content of Imports and the Foreign Content of Exports - National Research Council
Mass media has frequently covered stories concerning \

The Competitive Status of the U.S. Steel Industry - National Academy of Engineering; National Research Council (The National Academies Press, 1985)
This volume examines the influences of technology and international trade policies on the troubled U.S. steel industry. Does leadership in technology guarantee competitive advantage in industrial markets? Or do the costs of production and the lack of investment capital offset technological gains for the domestic steel industry? Which international trade policies can help this industry, and which may be harming it? With these and other questions in view, The Competitive Status of the U.S. Steel Industry estimates global trends in steel trade, discusses patterns of production and consumption, and analyzes the possible effects of alternative governmental policies on this critically important industry.

Behind the Numbers: U.S. Trade in the World Economy - National Research Council (The National Academies Press, 1992)
America's international economic decisions rest to a large degree on the information available to policymakers. Yet the quality of international trade and financial data is in serious doubt. This book reveals how our systems for collecting and analyzing trade data have fallen behind the times2014and presents recommendations for new approaches to accuracy and usefulness of these economic data. The volume traces the burgeoning use of international economic data by public and private analysts at a time when the United States is becoming increasingly integrated into the world economy. It also points out problems of capturing new transactions, comparing data from different sources, limited access to the data, and more. This is the first volume to review all three types of U.S. international data2014merchandise trade, international services transactions, and capital flows. Highlights include: Specific steps for U.S. agencies to take. Special analyses on improving the accuracy of merchandise trade data, filling data gaps on the fast-growing international services transactions, and understanding structural changes in world capital markets. Comments, complaints, and suggestions from an original survey of more than 100 key users of trade data. This practical volume will be invaluable to policymakers, government officials, business executives, economists, statisticians, and researchers.

Conflict and Cooperation in National Competition for High-Technology Industry - National Research Council (The National Academies Press, 1996)
This unique volume contains a powerful set of recommendations on issues at the center of international discussions on investment, trade, and technology policy. They take into account the globalization of industrial activity and the special characteristics of high-technology industries while recognizing the continued policy role of national governments. The book identifies the rationale for promotional measures for high-technology industries, delineates sources of friction among the leading industrial countries, and proposes policies to enhance international cooperation and strengthen the multilateral trading regime. This volume also examines the factors driving collaboration among otherwise competing firms and national programs, highlights the need to develop principles of equitable public and private international cooperation, and emphasizes the linkage between investment, government procurement, and other trade policies and prospects for enhanced international cooperation.

Crew Size and Maritime Safety (The National Academies Press, 1990)
U.S. oceangoing vessels have half the crew size of 30 years ago, thanks to automation and mechanization in the shipping industry. But are reductions in crew size increasing the risk of vessel accidents? Crew Size and Maritime Safety explores how we can minimize risk without hindering technology, presenting the most thorough analysis available of key issues such as domestic versus foreign manning practices and safety performance; effect of crew size on crew fatigue, level of training, and ship maintenance; and modernizing the U.S. Coast Guard approach to crew size regulation. The volume features a trend analysis of 20 years of maritime safety data, analyzing U.S. and international laws and treaties concerning ship manning and making recommendations for improvements. In addition, it includes a model for setting optimum crew levels, based on systems engineering and tested with actual ships.

Developing Human Capital to Support U.S. Innovation Capacity: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Domestic and international competition for STEM talent is driving institutions across the research and innovation landscape to consider new policies and partnerships for building and managing STEM knowledge and skills. New levels of investment in human capital to increase U.S. innovation capacity and competitiveness will require coordination and collaboration among academic institutions, workforce development programs, labor organizations, companies, and funders of research and education. On October 18-19, 2022, the Government-University-Industry Research Roundtable convened a workshop for its membership and invited guests to consider the strategic priority of human capital investment in preparing the future workforce and supporting national innovation capacity. The workshop discussions examined the state of U.S. workforce preparation and considered trends in supply and demand for human capital to meet the needs of a transforming research enterprise. This publication summarizes the presentation and discussion of the workshop.

A Ready and Resilient Workforce for the Department of Homeland Security: Protecting America's Front Line - Institute of Medicine (The National Academies Press, 2013)
The responsibilities of the Department of Homeland Security (DHS) range from preventing foreign and domestic terrorist attacks; securing the nation's borders; safeguarding transportation systems; responding to natural disasters; nuclear detection; and more. Created in 2002 from a merger that rapidly incorporated parts of eight cabinet departments and 22 government agencies, DHS has struggled to integrate its numerous components and their unique cultures. While DHS is very accomplished at performing its many missions, the nature of the DHS work environment is inherently stressful, and employees suffer from low morale. A Ready and Resilient Workforce for the Department of Homeland Security: Protecting America's Front Line reviews current workforce resilience efforts, identifies gaps, and provides recommendations for a 5-year strategy to improve DHSTogether, the current DHS workforce resilience program. This report stresses the importance of strong leadership, communication, measurement, and evaluation in the organization and recommends content for a 5-year plan that will promote centralized strategic direction and resource investment to improve readiness and resilience at the department. While all DHS component agencies share a common mission, each have distinct roles with different stressors attached, making implementation of an organization-wide resilience or wellness program difficult. The recommendations of A Ready and Resilient Workforce for the Department of Homeland Security outline how DHS can focus its efforts on creating a common culture of workforce readiness and resilience, while recognizing the distinct, proud, celebrated cultures of its component agencies.

Choosing the Nation's Fiscal Future - National Research Council (The National Academies Press, 2010)
A mismatch between the federal government's revenues and spending, now and in the foreseeable future, requires heavy borrowing, leading to a large and increasing federal debt. That increasing debt raises a serious challenge to all of the goals that various people expect their government to pursue. It also raises questions about the nation's future wealth and whether too much debt could lead to higher interest rates and even to loss of confidence in the nation's long-term ability and commitment to honor its obligations. Many analysts have concluded that the trajectory of the federal budget set by current policies cannot be sustained. In light of these projections, Choosing the Nation's Fiscal Future assesses the options and possibilities for a sustainable federal budget. This comprehensive book considers a range of policy changes that could help put the budget on a sustainable path: reforms to reduce the rate of growth in spending for Medicare and Medicaid; options to reduce the growth rate of Social Security benefits or raise payroll taxes; and changes in many other government spending programs and tax policies. The book also examines how the federal budget process could be revised to be more far sighted and to hold leaders accountable for responsible stewardship of the nation's fiscal future. Choosing the Nation's Fiscal Future will provide readers with a practical framework to assess budget proposals for their consistency with long-term fiscal stability. It will help them assess what policy changes they want, consistent with their own values and their views of the proper role of the government and within the constraints of a responsible national budget. It will show how the perhaps difficult but possible policy changes could be combined to produce a wide range of budget scenarios to bring revenues and spending into alignment for the long term. This book will be uniquely valuable to everyone concerned about the current and projected fiscal health of the nation.

Emerging Workforce Trends in the U.S. Energy and Mining Industries: A Call to Action - National Research Council (The National Academies Press, 2013)
Energy and mineral resources are essential for the nation's fundamental functions, its economy, and security. Nonfuel minerals are essential for the existence and operations of products that are used by people every day and are provided by various sectors of the mining industry. Energy in the United States is provided from a variety of resources including fossil fuels, and renewable and nuclear energy, all with established commercial industry bases. The United States is the largest electric power producer in the world. The overall value added to the U.S. gross domestic product (GDP) in 2011 by major industries that consumed processed nonfuel mineral materials was 2.2 trillion. Recognizing the importance of understanding the state of the energy and mining workforce in the United States to assure a trained and skilled workforce of sufficient size for the future, the Department of Energy's (DOE's) National Energy technology Laboratory (NETL) contracted with the National Research Council (NRC) to perform a study of the emerging workforce trends in the U.S. energy and mining industries. Emerging Workforce Trends in the U.S. Energy and Mining Industries: A Call to Action summarizes the findings of this study.

Meeting Global Challenges: German-U.S. Innovation Policy: Summary of a Symposium - National Research Council (The National Academies Press, 2012)
While nations have always competed for territory, mineral riches, water, and other physical assets, they compete most vigorously today for technology-based innovations and the value that flows from them. Much of this value is based on creating scientific knowledge and transforming it into new products and services for the market. This process of innovation is complex and interdisciplinary. Sometimes it draws on the genius of individuals, but even then it requires sustained collective effort, often underpinned by significant national investments. Capturing the value of these investments to spur domestic economic growth and employment is a challenge in a world where the outputs of innovation disseminate rapidly. Those equipped to understand, apply, and profit from new knowledge and technical advances are increasingly able to capture the long-term economic benefits of growth and employment. In response to this new, more distributed innovation paradigm, the National Academies Board on Science, Technology, and Economic Policy (STEP) convened leading academics, business leaders, and senior policymakers from Germany and the United States to examine the strengths and challenges of their innovation systems. More specifically, they met to compare their respective approaches to innovation, to learn from their counterparts about best practices and shared challenges, and to identify cooperative opportunities. The symposium was held in Berlin and organized jointly by the German Institute for Economic Research (DIW) and the U.S. National Academies with support of the German Federal Ministry for Education and Research (BMBF) and the American Embassy in Berlin. Both U.S. and German participants described common challenges on a wide variety of issues ranging from energy security and climate change to low-emissions transportation, early-stage financing, and workforce training. While recognizing their differences in approach to these challenges, participants on both sides drew out valuable lessons from each other's policies and practices. Participants were also aware of the need to adapt to a new global environment where many countries have focused new policy measures and new resources to support innovative firms and promising industries. Meeting Global Challenges: U.S.-German Innovation Policy reviews the participants meeting and sets goals and recommendations for future policy.